Endogean and cavernicolous Coleoptera of the Balkans. XVIII. Strong radiation in caves of the Central Dinarides: seven new species of Thaumastocephalus Poggi et al., 2001 (Staphylinidae: Pselaphinae) - Hlaváč, Peter; Bregović, Petra; Jalžić, Branko (Zootaxa, 2019)
Seven new species of the cavernicolous and anophthalmous genus Thaumastocephalus Poggi, Nonveiller, Colla, Pavićević & T. Rađa, 2001 are described: T. bilandzijae sp. n., T. kirini sp. n., T. marsici sp. n., T. rujnicensis sp. n., T. slavkoi sp. n. and T. troglavi sp. n. from Croatia and T. dahnae sp. n. from Bosnia and Herzegovina. Aedeagi of all species are illustrated. A key to all species is provided. The records of all specimens of the genus treated here are given, and their distributions are discussed and shown on maps. The distribution of all genera of cavernicolous Pselaphinae in the Dinarides is discussed.